Influence of Adjunct Cultures of Lactobacillus spp. on Chemical, Microbiological and Sensory Properties of White Pickled Cheese - Kaptan, B.; Kurultay, S.; Bilgin, B. (Asian Journal of Chemistry, 2010)
This paper reports a comparison of changes in the microflora and chemical parameters related with Lactococcus and Lactobacillus cultures during 90 days ripening in Turkish white pickled cheese. One control (K) and four experimental cheeses were manufactured by the addition of Lactobacillus casei (A) 1 % and (B) 106 cfu mL-1 and Lactobacillus plantarum (E) 1 % and (F) 106 cfu mL-1 plus commercial starter culture comprising Lactococcus lactis subsp. lactis and Lactococcus lactis subsp. cremoris. As a result of the ripening process, all the sensorial, microbiological and chemical characteristics were significantly affected and some Lactobacillus ssp. might be considered suitable as adjunct cultures in the Turkish white pickled cheese production process because of their positive contribution to cheese flavour.